Data-Driven Self-Portraits: Intimate connections with urban information - Barriga-Abril, Xavier (Street Art & Urban Creativity, 2025)
A set of data-driven sculptures has been implemented in the city of Quito. These interventions visualize the movement of urban cyclists. To create them, a series of interfaces were designed to record and present their movement. This article explores the author’s personal connection with Quito by creating personalized maps that trace their most significant cycling routes. During this process, the author reflects on the tension between objectivity and subjectivity in urban research. By employing an autoethnographic methodology and using data-driven self-portraits, a more intimate relationship with the data is promoted, encouraging more humanized and diverse interpretations. This approach contributes to building a more pluralistic vision of the city, distancing itself from colonial perspectives. This proposal adds to the debate on creative cities, highlighting the need for new formats of representations to study the multiple forms of connectivity in the city.